Effect of Tolfenamic Acid on Conception Rate Following Embryo Transfer in Cattle - Mayank Maithani; Shiv Prasad; Sunil Kumar; Ankit Malik (The Indian Veterinary Journal, 2024)
The present study was designed to see the effect of tolfenamic acid, an anti-inflammatory drug on conception rate of crossbred embryo recipient following embryo transfer from Sahiwal cows.  H.F Crossbred cows were selected and divided into three groups, control (n=6): NSS, T1 (n=6): (tolfenamic acid @4mg/kg bwt, I.M 1 hr before transfer) and T2(n=6): tolfenamic acid @4mg/kg bwt,I.M 1 hr before transfer and during 15th and 16th days of estrous cycle. Blood samples were number of C.L, Total embryo (TE), Blastocyst (Bl), Morula (M) and degenerated embryo per collected on 7, 15, 16,17th and 32nd days of estrous cycle. The serum samples were separated and stored at -20 degree Celsius until analysis of hormones (PGFM and Progesterone via ELISA and RIA kit respectively) and biochemical parameters. The superovulatory response was measured as superovulatory treatment (ST) and was 15.11±0.96, 4.25±0.98, 4±0.94, 1 and 1respectively. The embryo recovery rate was 25%. The mean value of serum PGFM decreased significantly in the T2 group during all days of sample collection and progesterone concentration increased in the T2 group. In this study, a total of 3 pregnancies  were  achieved, one in each group with an overall conception rate of 16.6%.  It can be concluded that tolfenamic acid is effective in reducing PGFM and increasing progesterone concentration during the luteal phase of the estrous cycle, which is beneficial in improving conception rate following embryo transfer as evident by PGFM and progesterone. More studies with better conceptions rate are required to validate these findings.